Flame retardant and preparation method and application thereof, flame retardant adhesive and preparation method thereof
Benzooxazine was solved by using glycidylamine-type epoxy resin and flame retardant prepared by 9,10-dihydro-9-oxa-10-phosphophenol-10-oxide in benzoxazine resin The problem of poor flame retardant performance of the zine resin achieves the effect of significantly improving its flame retardant performance while maintaining thermal stability and mechanical properties.
Patent Information
- Application Number
- CN202210894888.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-07-28
AI Technical Summary
Benzoxazine resins have poor flame retardant properties in industrial applications, which lead to their limitations in some applications.
A new flame retardant is used, which is prepared by polycondensation reaction of glycidylamine type epoxy resin and 9,10-dihydro-9-oxa-10-phosphophenophen-10-oxide, with The rigid benzene ring structure and highly reactive epoxy groups can cure and cross-link with the benzoxazine resin matrix, improving its flame retardant properties.
On the basis of improving the flame retardant performance, the flame retardant can maintain or small losses of the thermal stability and mechanical properties of the benzoxazine resin, achieving an improvement in the flame retardant performance without damaging the other properties of the resin.
Smart Images

Figure CN115651024B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardancy, and specifically relates to a flame retardant and a preparation method and application thereof, a flame retardant adhesive and a preparation method thereof. Background Art
[0002] Benzoxazine is a six-membered heterocyclic compound synthesized by Mannich reaction from phenolic compounds, amine compounds and aldehyde compounds. It can undergo ring-opening polymerization under heating or the action of a catalyst to generate a benzoxazine resin with a network structure similar to that of phenolic resin. Since the curing process does not require the addition of strong acid or strong base catalysts, there is no small molecule release during the polymerization process, and the cured resin has excellent mechanical properties, thermal properties and electrical insulation, it is widely used in technical fields such as lithium battery electrode binders. However, benzoxazine resin also has the disadvantage of poor flame retardancy, which limits its further development in industrial applications.
[0003] Traditional flame retardant modification mainly involves adding flame retardants to benzoxazine resins. Although the flame retardants can make the benzoxazine resins obtain excellent flame retardant effects, they largely lose the thermal stability and mechanical properties of the resins. Summary of the invention
[0004] The purpose of the present invention is to provide a flame retardant and a preparation method and application thereof, a flame retardant adhesive and a preparation method thereof. The flame retardant provided by the present invention is applied to a benzoxazine resin matrix, and can improve the flame retardant performance without losing or losing thermal stability and mechanical properties to a small extent.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a flame retardant, wherein the flame retardant is a structural compound represented by Formula I or Formula II:
[0007]
[0008] In the formula I, R1 to R4 are independently And R1~R4 are not the same
[0009]
[0010] In the formula II, R7 is The R5 or R6 is independently And R5≠R6.
[0011] The present invention also provides a method for preparing the flame retardant described in the above technical solution, comprising the following steps:
[0012] The flame retardant is obtained by mixing a glycidylamine epoxy resin and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and subjecting the mixture to a polycondensation reaction;
[0013] The glycidylamine epoxy resin is a structural compound represented by formula III or formula IV:
[0014]
[0015] In the formula III to IV, R is
[0016] Preferably, the molar ratio of the glycidylamine epoxy resin to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:1-4.
[0017] Preferably, the polycondensation reaction is carried out under a protective atmosphere.
[0018] Preferably, the polycondensation reaction is carried out at a temperature of 120 to 125° C. and for a time of 3 to 4 hours.
[0019] The present invention also provides the use of the flame retardant described in the above technical solution or the flame retardant prepared by the preparation method described in the above technical solution in the preparation of flame retardant materials.
[0020] The present invention also provides a flame retardant adhesive, comprising the following components in parts by weight:
[0021] 100 parts of benzoxazine resin and 1 to 50 parts of flame retardant;
[0022] The flame retardant is the flame retardant described in the above technical solution or the flame retardant prepared by the preparation method described in the above technical solution.
[0023] Preferably, the benzoxazine resin includes one or more of monocyclic benzoxazine, bisphenol benzoxazine and diamine benzoxazine.
[0024] The present invention also provides a method for preparing the flame retardant adhesive described in the above technical solution, comprising the following steps:
[0025] The benzoxazine resin and the flame retardant are mixed to obtain the flame retardant adhesive.
[0026] Preferably, the mixing temperature is 100-140°C.
[0027] The present invention provides a flame retardant, which is a structural compound shown in Formula I or Formula II. The flame retardant provided by the present invention has a rigid benzene ring structure, so that the flame retardant has excellent heat resistance; at the same time, it contains a highly reactive epoxy group; when the flame retardant is applied to a benzoxazine resin, the rigid benzene ring structure can improve the heat resistance stability of the adhesive; at the same time, the flame retardant can be cured and cross-linked with the benzoxazine resin matrix, introduce a highly reactive epoxy group, improve the cohesive force between molecules, and enhance the mechanical properties. Therefore, the flame retardant provided by the present invention can improve the flame retardant performance without losing or to a lesser extent losing thermal stability and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the infrared spectrum test diagram of the flame retardant obtained in Example 1;
[0029] Figure 2 This is a physical picture of the residual carbon after the flame retardant adhesive obtained in Example 1 is burned, wherein Figure 2 c is the main view, Figure 2 d is a top view;
[0030] Figure 3 This is a physical picture of the residual carbon after the flame retardant adhesive obtained in Comparative Example 1 is burned, where Figure 3 a is the main view, Figure 3 b is a top view;
[0031] Figure 4 This is a SEM image of the residual carbon after the flame retardant adhesive obtained in Example 1 was burned;
[0032] Figure 5 This is a SEM image of the carbon residue after burning the flame retardant adhesive obtained in Comparative Example 1;
[0033] Figure 6 DMA test chart of the flame retardant adhesive obtained in Examples 1 to 3 and Comparative Example 1;
[0034] Figure 7 This is a graph showing the bending performance test results of the flame retardant adhesives obtained in Examples 1 to 3 and Comparative Examples 1 to 2. DETAILED DESCRIPTION
[0035] The present invention provides a flame retardant, wherein the flame retardant is a structural compound represented by Formula I or Formula II:
[0036]
[0037] In the formula I, R1 to R4 are independently And R1~R4 are not the same
[0038]
[0039] In the formula II, R7 is The R5 or R6 is independently And R5≠R6.
[0040] The present invention also provides a method for preparing the flame retardant described in the above technical solution, comprising the following steps:
[0041] The flame retardant is obtained by mixing a glycidylamine epoxy resin and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and subjecting the mixture to a polycondensation reaction;
[0042] The glycidylamine epoxy resin is a structural compound represented by formula III or formula IV:
[0043]
[0044] In the formula III to IV, R is
[0045] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0046] In the present invention, the structural formula of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) is preferably as shown in Formula V:
[0047]
[0048] In the present invention, the molar ratio of the glycidylamine epoxy resin to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is preferably 1:1-4, and more preferably 1:2-3.
[0049] In the present invention, the mixing temperature is preferably 90-95°C, more preferably 91-94°C, and more preferably 92-93°C; the heating rate to the mixing temperature is preferably 5°C / min; the holding time is preferably 0.5h. In the present invention, the mixing is preferably carried out under a protective atmosphere; the protective atmosphere is preferably nitrogen. In the present invention, the mixing is preferably carried out under stirring; the stirring speed is preferably 180-220r / min. In the present invention, the mixed solution obtained after the mixing is completed is preferably transparent.
[0050] In the present invention, the polycondensation reaction is preferably carried out under a protective atmosphere; the protective atmosphere is preferably nitrogen. In the present invention, the temperature of the polycondensation reaction is preferably 120-125°C, more preferably 121-124°C, more preferably 122-123°C; the insulation time is preferably 3-4h. In the present invention, the polycondensation reaction is preferably carried out under stirring; the stirring speed is preferably 180-220 r / min. In the present invention, the polycondensation reaction is preferably carried out in a reactor with a reflux condensing device.
[0051] In the present invention, when the glycidylamine epoxy resin has a structure shown in Formula III, the reaction flow of the polycondensation reaction process is preferably:
[0052]
[0053] In the present invention, when the glycidylamine epoxy resin has a structure shown in Formula IV, the reaction process of the polycondensation reaction is preferably:
[0054]
[0055] After the polycondensation reaction is completed, the present invention also preferably includes post-processing the product obtained by the reaction; the post-processing preferably includes cooling, grinding, washing and drying. The present invention has no special limitation on the cooling, grinding, washing and drying process, and the process well known to those skilled in the art can be used.
[0056] In the present invention, the yield of the flame retardant is preferably 85-90%. In the present invention, the flame retardant is preferably in the form of light yellow powder.
[0057] The present invention also provides the use of the flame retardant described in the above technical solution or the flame retardant prepared by the preparation method described in the above technical solution in the preparation of flame retardant materials. The present invention has no special limitation on the specific implementation of the application, and those familiar to those skilled in the art can be used.
[0058] The present invention also provides a flame retardant adhesive, comprising the following components in parts by weight:
[0059] 100 parts of benzoxazine resin and 1 to 50 parts of flame retardant;
[0060] The flame retardant is the flame retardant described in the above technical solution or the flame retardant prepared by the preparation method described in the above technical solution.
[0061] In parts by mass, the flame retardant adhesive includes 100 parts of benzoxazine resin. In the present invention, the benzoxazine resin preferably includes one or more of a monocyclic benzoxazine resin, a bisphenol benzoxazine resin and a diamine benzoxazine resin.
[0062] In the present invention, the monocyclic benzoxazine resin preferably has the structure shown in VI:
[0063] The R9 is preferably H, methyl or ethyl; 10 Preferred is H, methyl, phenyl or cyclohexyl.
[0064] In the present invention, the bisphenol-type benzoxazine resin preferably has a structure shown in Formula VII:
[0065] The R 11 Preferably -O-, -CH2- or -C(CH3)2-; said R 12 Preferred is H, methyl or ethyl.
[0066] In the present invention, the diamine-type benzoxazine resin preferably has the structure shown in VIII:
[0067] The R 13 Preferably -O- or -CH2-; said R 14 Preferred is H, methyl or ethyl.
[0068] The present invention also provides a method for preparing the flame retardant adhesive described in the above technical solution, comprising the following steps:
[0069] The benzoxazine resin and the flame retardant are mixed to obtain the flame retardant adhesive.
[0070] In the present invention, the mixing temperature is preferably 100-140° C., more preferably 110-130° C., and more preferably 120° C. In the present invention, the mixing is preferably carried out under stirring; the stirring speed is preferably 300 r / min, the stirring time is preferably 5-30 min, more preferably 10-25 min, and more preferably 12-20 min.
[0071] After the mixing is completed, the present invention also preferably includes vacuuming the obtained mixture to remove bubbles. In the present invention, the temperature during the vacuuming and degassing is preferably 130-140° C. The present invention has no special limitation on the vacuuming and degassing process, and it can be carried out by a method well known to those skilled in the art.
[0072] After the vacuuming and degassing is completed, the present invention also preferably includes cooling the obtained material to room temperature. The present invention has no particular limitation on the cooling method, and any method known to those skilled in the art can be used.
[0073] In order to further illustrate the present invention, a flame retardant and its preparation method and application, a flame retardant adhesive and its preparation method provided by the present invention are described in detail below in conjunction with the drawings and embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0074] Example 1
[0075] 54g of glycidylamine epoxy resin of the structure shown in Formula III and 21.6g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were placed in a reactor equipped with a reflux condenser, heated and stirred at a speed of 200r / min under a nitrogen atmosphere, and heated to 95°C at a heating rate of 5°C / min, and kept warm for 0.5h until the system became transparent; then heated to 125°C at a heating rate of 5°C / min, and kept warm for 3h to carry out polycondensation reaction; after the reaction was completed, cooled to room temperature, ground, washed and dried to obtain a light yellow powder flame retardant with a yield of 85%;
[0076] 10g of flame retardant and 100g of benzoxazine resin were mixed, and the mixture was heated to 120°C in an air atmosphere at a speed of 300r / min to melt until it became transparent; the obtained mixed solution was transferred to a vacuum oven, and vacuumed at 140°C to remove bubbles; after the reaction was completed, the mixture was cooled to room temperature to obtain a flame retardant adhesive;
[0077] The benzoxazine resin has a structure as described in Formula 1:
[0078]
[0079] Example 2
[0080] A flame retardant was prepared in the manner of Example 1;
[0081] 20 g of flame retardant and 100 g of benzoxazine resin (benzoxazine resin having a structure shown in Formula 1 described in Example 1) were mixed, heated to 120° C. in an air atmosphere at a speed of 300 r / min and melted until transparent; the obtained mixed solution was then transferred to a vacuum oven and vacuumed at 140° C. to remove bubbles; after the reaction was completed, the mixture was cooled to room temperature to obtain a flame retardant adhesive.
[0082] Example 3
[0083] A flame retardant was prepared in the manner of Example 1;
[0084] 30 g of flame retardant and 100 g of benzoxazine resin (benzoxazine resin having a structure shown in Formula 1 described in Example 1) were mixed, heated to 120° C. in an air atmosphere at a speed of 300 r / min and melted until transparent; the obtained mixed solution was then transferred to a vacuum oven and vacuumed at 140° C. to remove bubbles; after the reaction was completed, the mixture was cooled to room temperature to obtain a flame retardant adhesive.
[0085] Comparative Example 1
[0086] 100 g of benzoxazine resin (the benzoxazine resin having the structure shown in Formula 1 described in Example 1) was heated to 120° C. in an air atmosphere at a rotation speed of 300 r / min and melted until it became transparent; the obtained mixed solution was then transferred to a vacuum oven and evacuated at 140° C. to remove bubbles; after the reaction was completed, the mixture was cooled to room temperature to obtain an adhesive.
[0087] Comparative Example 2
[0088] 10 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and 100 g of benzoxazine resin (the benzoxazine resin having the structure shown in Formula 1 described in Example 1) were mixed, heated to 120° C. in an air atmosphere at a speed of 300 r / min and melted until transparent; the obtained mixed solution was transferred to a vacuum oven, and vacuumed at 140° C. to remove bubbles; after the reaction was completed, the mixture was cooled to room temperature to obtain a flame retardant adhesive.
[0089] Performance Testing
[0090] Test Example 1
[0091] The flame retardant (ED) obtained in Example 1 was subjected to infrared spectrum test. The test method was as follows: the flame retardant (ED) obtained in Example 1 was tested by using a Nicolet IS5 Fourier transform infrared spectrometer of the American Thermo Electric Company. The sample to be tested was mixed with KBr and then pressed into a tablet to obtain a test sample. The test range was 4000-400 cm -1 ; Test results such as Figure 1 As shown, from Figure 1 It can be seen that the flame retardant obtained in this example does not appear at 2436 cm in the DOPO spectrum. -1 The characteristic absorption peak of PH bond is at 3400cm -1 The characteristic absorption peak of -OH bond appeared nearby, indicating that the PH bond of DOPO reacted with the epoxy group of glycidylamine epoxy resin to form hydroxyl group.
[0092] Test Example 2
[0093] The adhesives obtained in Examples 1 to 3 and Comparative Examples 1 and 2 were cured at 170° C. for 1 h, 180° C. for 2 h, 200° C. for 2 h, and 210° C. for 1 h to obtain test samples;
[0094] The obtained test sample was subjected to a vertical combustion test. The test method is: using a vertical combustion instrument model FRT-503 of Shanghai Precision Scientific Instrument Co., Ltd., and testing according to the UL94 vertical combustion standard. The sample size is: 120mm×10mm×4mm. The test results are shown in Table 1.
[0095] Table 1 Vertical combustion test results of adhesives obtained in Examples 1 to 3 and Comparative Example 1
[0096]
[0097] Note: t1 represents the self-extinguishing time 10 seconds after the first ignition, t2 represents the self-extinguishing time 10 seconds after the second ignition, Dripping represents molten drop, and Rating represents rating;
[0098] As can be seen from Table 1, the blank benzoxazine resin in Comparative Example 1 itself has no flame retardancy and has no UL-94 grade; while the flame retardant adhesive provided in the present application has improved flame retardancy and reaches UL-94 V-0 grade.
[0099] The actual picture of the carbon residue after the burning of the adhesive obtained in Example 1 is as follows: Figure 2 As shown, Figure 2 c is the main view, Figure 2 d is a top view; the actual picture of the carbon residue after burning of the adhesive obtained in Comparative Example 1 is as follows Figure 3 As shown, Figure 3 a is the main view, Figure 3 b is a top view; Figure 2 and 3 It can be seen that the carbon layer of the blank benzoxazine resin cracks after combustion; when the flame retardant is added, a dense and continuous carbon layer is formed after combustion. The carbon layer dehydrates while expanding, and releases gas when exposed to heat or air. Under the action of the gas, an expanded carbon layer structure surrounded by fluffy pores is formed. The carbon layer is non-flammable and acts as a barrier to heat, air and hydrolysis products. When there is insufficient oxygen and heat in the environment, the combustion of the polymer is difficult to proceed, resulting in self-extinguishing.
[0100] The SEM image of the carbon residue after burning the adhesive obtained in Example 1 is as follows: Figure 4 As shown, Figure 4 f is the SEM image with a scale of 500 μm. Figure 4 h is the SEM image with a scale of 100 μm; the SEM image of the residual carbon after the adhesive combustion obtained in Comparative Example 1 is as follows Figure 5 As shown, Figure 5 e is the SEM image with a scale of 500 μm. Figure 5 g is the SEM image with a scale of 100 μm. Figure 4 and 5 It can be seen that after the blank benzoxazine resin is burned, the carbon layer surface is loose and has many cracks, and the internal section is expanded with many bubbles and the bubbles are large; while the surface of the benzoxazine resin containing the flame retardant has no cracks after burning, and is denser than the blank benzoxazine resin. This dense outer surface is conducive to blocking the combustible gas from entering the interior of the sample and improving its flame retardant properties. At the same time, the internal section of the burning sample of the benzoxazine resin containing the flame retardant forms a honeycomb-like hole structure, which may be due to the release of some blown-out gases during the combustion process, which greatly improves the flame retardant effect.
[0101] Test Example 3
[0102] The adhesives obtained in Examples 1 to 3 and Comparative Example 1 were cured at 170° C. for 1 h, 180° C. for 2 h, 200° C. for 2 h, and 210° C. for 1 h to obtain test samples;
[0103] The obtained test sample was subjected to the limiting oxygen index LOI test. The test method is: using the oxygen index tester model JF-3 of Jiangsu Zhengrui Taibang Electronic Technology Co., Ltd. for testing. The sample size is: 120mm×10mm×4mm. The test results are shown in Table 2.
[0104] Table 2 Limiting oxygen index test results of adhesives obtained in Examples 1 to 3 and Comparative Example 1
[0105] Example 1 Example 2 Example 3 Comparative Example 1 LOI 28.5% 32.4% 37.1% 23.8%
[0106] It can be seen from Table 2 that the LOI of the blank benzoxazine resin in Comparative Example 1 is a flammable grade, while the LOI of the flame retardant adhesive obtained in the present application is a flame retardant grade.
[0107] Test Example 4
[0108] The adhesives obtained in Examples 1 to 3 and Comparative Example 1 were cured at 170° C. for 1 h, 180° C. for 2 h, 200° C. for 2 h, and 210° C. for 1 h to obtain test samples;
[0109] The obtained samples were subjected to cone calorimetry test. The test method is as follows: using a cone calorimeter from Fire Test Technology of the United Kingdom, the test was carried out in accordance with ISO 5660-1, the sample size was: 100 mm × 100 mm × 4 mm, the radiation heat flux was 50 kW / m 2 ,The test results are shown in Table 3;
[0110] Table 3 Cone calorimetry test results of adhesives obtained in Examples 1 to 3 and Comparative Example 1
[0111]
[0112]
[0113] It can be seen from Table 3 that the flame retardant adhesive provided by the present invention has excellent flame retardant properties compared with the blank benzoxazine resin in Comparative Example 1; and with the increase of the flame retardant content, the ignition time (TTI) of the flame retardant adhesive increases, the total heat release (THR) decreases, the peak heat release rate (pk-HRR) decreases, the average effective heat of combustion (av-EHC) decreases, the average specific extinction area (av-SEA) increases, and the flame retardant performance is improved.
[0114] Test Example 5
[0115] The adhesives obtained in Examples 1 to 3 and Comparative Examples 1 and 2 were cured at 170° C. for 1 h, 180° C. for 2 h, 200° C. for 2 h, and 210° C. for 1 h to obtain test samples;
[0116] The flame retardant in Example 1 was cured to obtain a sample to be tested. The curing conditions were as follows: the flame retardant and methyltetrahydrophthalic anhydride were mixed in an equivalent ratio, and the mixture was kept at 120° C. for 1 h, 140° C. for 2 h, and 160° C. for 2 h for a curing reaction to obtain a sample to be tested.
[0117] The above-obtained test samples were subjected to thermogravimetric analysis test. The test method is: using a thermogravimetric analyzer model TG209F1 produced by NETZSCH Instrument Manufacturing Co., Ltd. of Germany for testing. The test conditions are: N2 atmosphere, flow rate of 100 mL / min, heating rate of 10°C / min. The test results are shown in Table 4.
[0118] Table 4 Thermogravimetric test results of the adhesives obtained in Examples 1 to 3 and Comparative Examples 1 and 2
[0119]
[0120]
[0121] It can be seen from Table 4 that the blank benzoxazine resin in Comparative Example 1 has good thermal stability. The temperature (T d5% ) is 318.6°C. After the flame retardant DOPO is directly added in Comparative Example 2, the T d5% The initial thermal performance is reduced to only 218.5°C. However, after adding the flame retardant provided by the present invention, the Td5% The temperature of the benzoxazine resin decreased, but the decrease was small (< 5%), and the flame retardant performance was greatly improved, which shows that the modification effect is excellent. The flame retardant performance of the resin is improved without losing the performance of the resin itself. In addition, after adding the flame retardant, the benzoxazine resin has two thermal decomposition peaks, of which the first decomposition peak temperature (T max1 ) is comparable to that of the blank resin, and the second decomposition peak temperature (T max2 ) is higher than that of blank resin, and the maximum thermal decomposition rate (V max ) decreases with the increase of flame retardant addition, and the residual carbon rate at 800℃ remains basically unchanged.
[0122] Test Example 6
[0123] The adhesives obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were cured at 170° C. for 1 h, 180° C. for 2 h, 200° C. for 2 h, and 210° C. for 1 h to obtain test samples;
[0124] The obtained samples were subjected to dynamic thermomechanical analysis (DMA) test. The test method is as follows: the dynamic thermomechanical properties of the blended system cured samples were tested using DMA Q800 analyzer from TAInstruments. The sample size is 60×12×3mm 3 The measurement temperature range is 25-250°C, the heating rate is 5°C / min, the frequency is 1Hz, and the mode is three-point bending mode; the test results are shown in Table 5 and Figure 6.
[0125] Table 5 DMA test results of adhesives obtained from Examples 1 to 3 and Comparative Examples 1 and 2
[0126] E′at30℃(MPa) <![CDATA[T gtanδ (℃)]]> Example 1 4871 200.0 Example 2 4921 191.6 Example 3 4980 186.4 Comparative Example 1 4665 211.3 Comparative Example 2 4150 159.5
[0127] As can be seen from the table, the dynamic modulus E' of the flame retardant adhesive provided by the present invention is basically consistent with that of the blank benzoxazine resin, indicating that the introduction of the flame retardant has little effect on the modulus of the benzoxazine resin. g Compared with the blank benzoxazine resin, it is slightly reduced, but the reduction is small; however, it is higher than Comparative Example 2, indicating that the flame retardant adhesive obtained by the present invention still has excellent heat resistance.
[0128] Test Example 7
[0129] The adhesives obtained in Examples 1 to 3 and Comparative Example 2 were cured at 170° C. for 1 h, 180° C. for 2 h, 200° C. for 2 h, and 210° C. for 1 h to obtain test samples;
[0130] The obtained samples were subjected to bending performance test. The test method is: using the Instron-3382 electronic universal material testing machine of INSTRON to test the mechanical properties of the cured samples. The test standard refers to GB / T2567-2008, the fulcrum span is 65mm, the speed is 2mm / min, and the sample size is 80×15×4mm 3 ; Test results such as Figure 7 shown.
[0131] Depend on Figure 7 It can be seen that the introduction of the flame retardant reduces the bending strength of the benzoxazine resin. The introduction of the flame retardant in Comparative Example 2 has a greater effect on the mechanical properties of the benzoxazine resin, and the bending strength decreases significantly. The effect of the flame retardant provided by the present invention on the mechanical properties of the benzoxazine resin is much smaller than that of Comparative Example 2, indicating that the flame retardant modification effect of the flame retardant provided by the present invention is better than that of the existing flame retardant.
[0132] In summary, when the flame retardant provided by the present invention is used to modify the benzoxazine resin, the flame retardancy is improved, while the high glass transition temperature and mechanical properties of the original resin itself are maintained, and the modification effect is excellent.
[0133] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A flame retardant adhesive, characterized in that: The components are: 100 parts of benzoxazine resin and 1-50 parts of flame retardant; The method for preparing the flame retardant comprises the following steps: The flame retardant is obtained by mixing a glycidylamine epoxy resin and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and subjecting the mixture to a polycondensation reaction; The glycidylamine epoxy resin is a compound having a structure shown in formula III: Formula III; In the formula III, R is .
2. The flame retardant adhesive according to claim 1, characterized in that: The molar ratio of the glycidylamine epoxy resin to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:1-4.
3. The flame retardant adhesive according to claim 1, characterized in that: The polycondensation reaction is carried out under a protective atmosphere.
4. The flame retardant adhesive according to claim 1, characterized in that: The temperature of the polycondensation reaction is 120-125° C. and the time is 3-4 hours.
5. The flame retardant adhesive according to claim 1, characterized in that: The benzoxazine resin includes one or more of monocyclic benzoxazine, bisphenol benzoxazine and diamine benzoxazine.
6. The method for preparing the flame retardant adhesive according to any one of claims 1 to 5, characterized in that: The following steps are involved: The benzoxazine resin and the flame retardant are mixed to obtain the flame retardant adhesive.
7. The preparation method according to claim 6, characterized in that: The mixing temperature is 100-140°C.